CULTURE ORGANIC FARMING: Sebuah Pengabdian dalam Upaya Pembentukan Karakter Petani terhadap Pengelolaan Padi Sawah Modern dan Berkelanjutan di Sulawesi Selatan - Eymal B Demmallino; Baharuddin Patandjengi; Yunus Musa (Jurnal Pengabdian Masyarakat Hasanuddin (JPMH), 2021)
This Community Service Program is motivated by the situation of rice field management problems in South Sulawesi and Bulukumba Regency in particular. Lowland rice productivity in South Sulawesi only ranged from 4,197 ~ 5,074 tons/ha or an average of 4,623 tons/ha (BPS, 1993 ~ 2011). The problem lies in: (1) the narrowness of the managed land due to the existence of land pragmentation in farming families and land conversion; (2) land fatigue due to continuous and even excessive use of chemical fertilizers, (3) low adoption of superior seeds due to misunderstandings from farmers regarding the seeds they plant and partly due to frequent failures of the seeds distributed; (4) increasing pest and disease attacks due to the use of various and excessive pesticides, (5) weak regeneration of farmers due to the lack of interest in agricultural graduates to return to farming. This service program recommends a comprehensive solution by combining technological engineering (adoption of liquid organic fertilizer which has been patented by the Research and Development Center for Biotenology LPPM UNHAS under the name MOPlus Biological Fertilizer, adoption of superior hybrid seeds, efficient and effective control of water in farmland, and organic pest control). with social-institutional engineering (in terms of character building of farmers through direct assistance of the Expert Team in the management of lowland rice farming in a modern and sustainable manner). The results of this service program are an increase in productivity (35 ~ 50% of the previous production) and the growth of the nation's character (awareness of the interests of the national economy, scientific work or smart work, and concern for changing ways of thinking from moral choice to rational choice) in supporting increased productivity, competitiveness, and sustainability.